Photoluminescence and electrical conductivity measurement of liquid crystal doped with ZnO nanoparticles. Issue 5 (9th April 2019) - Pushpavathi, N.; Sandhya, K. L.; Pratibha, R.
ABSTRACT: We report the effect of dispersion of zinc oxide (ZnO) nanoparticles (NPs) on the conductivity, birefringence and fluorescence properties of commercially available room temperature nematic liquid crystal (LC) with the variation of dopant concentration. Significant changes have been observed in transition enthalpy, DC conductivity, photoluminescence and birefringence values of the LC material by the addition of ZnO NPs. While the inclusion of NPs enhances the electrical conductivity of the composite system, it results in a reduction in the birefringence value, which can be attributed to a decrease in the order parameter of the system due to the perturbed geometry of the LC. This also results in the increase in threshold voltage value, which has been speculated as due to the piezoelectric nature of the ZnO NPs. The analysis of the fluorescence spectrum indicates that ZnO NPs enhance the intensity in the LC phase along with a small blue shift. Graphical Abstract: